Increasing Children's Self-Confidence Through Coloring Competitions in Laban Village - Azkiyatun Nasiha; Dimas Faturrohman; Heny Cipto Wening; Iqbal Hasyim; Laili Zakiyatul Hanafiyah; Miftahul Hasanah; M. Abdul Azzam; M. Sekhan Khasan (Lembaga Pengembangan Kinerja Dosen, 2024)
Self-Esteem is an Important Aspect in Child Development, Particularly in Preschool Age (TK). One Way to Enhance Children's Self-Esteem is Through Coloring Contests, Where Children Can Express Their Creativity Freely. This Study Aims to Investigate the Impact of Coloring Contests on Increasing Children's Self-Esteem. The Methods Used Include Planning, Guidance, and Observation During the Conduct of the Coloring Contest Involving 153 Children from Several Educational Institutions. The Results Show That This Activity Not Only Fosters Enjoyment but Also Successfully Boosts Children's Self-Esteem. Children Feel Proud of Their Creations and Are More Confident in Expressing Themselves. The Coloring Contest Proves to Be an Effective Tool for Developing Children's Self-Esteem in Early Childhood.